Development of Intention to Stay Model for Temporary Nursing Staff in RS UNAIR - Ike Nesdia Rahmawati; Nursalam Nursalam; Ninuk Dian Kurniawati (Jurnal Ners, 2014)
Introduction: Intention to stay of nurses is important to reduce turnover rate and to improve the stability of hospital. Quality of nursing work life (QNWL) has been found to influence intention to stay. However, reliable information of this effect is limited. The purpose of this study was to develop the model of intention to stay for temporary nursing staff in RS UNAIR.Method: Anexplanative cross-sectional survey design was used in this study. Data were collected by using questionnaire among 32 nurses working at different units in this hospital through simple random sampling and analyzed by partial least square (PLS). Result: QNWL affected job satisfaction but did not affect commitment. Commitment was significantly affected by job satisfaction. There was effect of job satisfaction on intention to stay. Commitment also significantly affected intention to stayDiscussion: QNWL is a predictor of intention to stay trough job satisfaction and commitment. It is recommended that more focused interventions on QNWL, job satisfaction, and commitment developments may improve intention to stay. Recruitment of non-nursing staff to carry out billing and administrative tasks is urgently needed. Suggestions for further research is to analyze the effect of empowerment, remuneration, and career ladder on nurses’ intention to stay.